Os limites constitucionais da infiltração de agentes - Mathis, Ana Victoria de Paula Souza de (2014)
This thesis analyzes the institute of the undercover agent law within the context of the democratic criminal procedure, whose structural and axiological basis is the notion of human dignity. Organized crime is a reality and its handling requires the criminal procedure to provide effective solutions. This research is aimed at identifying whether the infiltration of agents as a special means of investigation, reserved for crimes committed by criminal organizations, is supported by the constitution. It concludes that it is both a highly efficient technique, as well as highly restrictive in terms of fundamental rights. For this reason, it is only accepted as a means of investigation in situations involving crimes of severe gravity, committed by criminal organizations, extremely difficult to investigate and clarify, and as long as the evidence cannot be obtained through alternative means. The constitutionality of the practice of infiltration of agents is defined by the limits of the actions of the Law enforcement agent himself, and for this reason there needs to be a very clear and precise Law defining such limits and actions. This study concludes that the infiltration of a law enforcement agent within a criminal organization, with the objective of investigating crimes, acting passively in regards to the committal of crimes, with a scope of actions limited to the collection of evidence and the observation of actions of other members of the aforementioned organization, is constitutional. On the other hand, the committal of crimes by such infiltrated law enforcement agent is accepted as long as it is proportional to the objectives of the investigation, with the infiltrated agent being liable for any excesses identified. This, however, does not include the practice of intentional crimes against life, sexual freedom or torture. Under no circumstances will the committal of such crimes be tolerated